RESPONSE OF GREENGRAM (Vigna radiata L.Wilczek) TO FOLIAR NUTRITION OF NANO UREA AND NANO DAP - P , VENKATA RAO (The Journal of Research ANGRAU, 2026)
A field experiment entitled was conducted during rabi 2022-23 at Regional Agricultural Research Station, ANGRAU, Lam, Andhra Pradesh, to study the response of greengram (Vigna radiata L.Wilczek) with foliar nutrition of nano urea and nano DAP.The experiment comprised of nine treatments and three replications with RBD design.The results indicated that foliar spray of nano DAP and nano urea resulted in higher grain yield (929 kg ha-1&900 kg ha-1) with yield advantage over control (water spray) 739 kg ha-1.The highest net returns and B:C ratios of Rs. 34056 /- & Rs. 31962/- and 0.92 & 0.86 were realized with foliar spray of nano DAP @1.25 ml/l and nano urea @ 2.5 ml/l at flowering initiation, respectively.